2007
DOI: 10.4025/actasciagron.v29i4.404
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento vegetativo de cultivares de café (<em>Coffea arabica</em> L.) e sua correlação com a produção em espaçamentos adensados

Abstract: No adensamento de plantio, ocorrem alterações fisiológicas no comportamento das plantas. Com o objetivo de compreender tais alterações, avaliaram-se os caracteres morfo-vegetativos das cultivares IAC 44, IAC 99, MG 1192, Katipó, MG 6851 e UFV 3880 nos espaçamentos de plantio 1,0; 1,5; 2,0 e 2,5 m entre linhas, e 0,75 m entre as plantas. O experimento foi realizado em esquema fatorial 4 (espaçamentos) x 6 (cultivares de café) com 6 repetições, em delineamento de blocos ao acaso. Aos 20 e 33 meses, avaliaram-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
2
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 0 publications
5
20
2
7
Order By: Relevance
“…In this study, production traits showed a high genetic correlation with vegetative variables (Table 2), as with other perennial species, for example, açaí (Farias Neto et al, 2005) and coffee (Freitas et al, 2007;Martinez et al, 2007 It was possible to verify a high positive genetic correlation between PH and NB, NF, NS, SD, and PS ( Table 2).…”
Section: Genetic Correlations and Path Analysismentioning
confidence: 69%
See 1 more Smart Citation
“…In this study, production traits showed a high genetic correlation with vegetative variables (Table 2), as with other perennial species, for example, açaí (Farias Neto et al, 2005) and coffee (Freitas et al, 2007;Martinez et al, 2007 It was possible to verify a high positive genetic correlation between PH and NB, NF, NS, SD, and PS ( Table 2).…”
Section: Genetic Correlations and Path Analysismentioning
confidence: 69%
“…Martinez et al (2007) and Carvalho et al (2010), who evaluated genotypes of Coffea arabica, and Costa et al (2008), who evaluated progenies of Hevea brasiliensis, also reported a high correlation between PH and first production.…”
Section: Genetic Correlations and Path Analysismentioning
confidence: 99%
“…The reduction in the fruit-bearing capacity of the trees with close spacing does not appear to be caused by a decrease in fruit setting (Kumar, 1979a), nor by a reduction in the number or length of plagiotropic branches (Nacif, 1997;Martinez et al, 2007). It may be attributed to the effect of shading on the number of fruits per node and possibly the number of fruit-bearing nodes, as already pointed out.…”
Section: High-density Plantingsmentioning
confidence: 79%
“…Manipulation of the number of trees per unit land area aims among other things the establishment of an adequate leaf area index for crop production, with an apparent optimal value about 7-8 for several cultivars of arabica coffee (Kuguru et al, 1978;Arcila and Chaves, 1995;Martinez et al, 2007). However, the optimal plant density for arabica coffee depends on several factors including cultivars, availability of water and nutrients, and air evaporative demand and temperature.…”
Section: High-density Plantingsmentioning
confidence: 99%
“…Carvalho et al (2010) evaluated the initial performance of 25 varieties of arabica coffee in the spacing of 3.5 × 0.7 m in three regions of Minas Gerais and report that the characteristics that showed higher phenotypic correlation with yield were the number of plagioropic branches, plant height and length of plagiotropic branches . Martinez et al (2007) studied four cultivars of arabica coffee in the city of Ervália -MG, and report that in the spacing of 2.5 × 0.75 m, the correlation between production and the number of plagiotropic branches was not significant at 48 months after planting. The vegetative characteristics of coffee satisfactorily explained the variation in productivity.…”
Section: Sv Dfmentioning
confidence: 99%